La necrópolis de La Molineta: aproximación a la historia social y económica en el Puerto de Mazarrón (Murcia) durante la Antigüedad Tardía - Amante Sánchez, Manuel; López Campuzano, Manuel (Antigüedad y Cristianismo, 1991)
The necropolis la Molineta is situated in the Puerto the Mazarrón (Murcia) and it is know since the year 1960. Since then diferent excavations have been done showning the demographic importance of this burial place dated between the four thand sixth century A.D. During the months of July 1990 the excavations of the St-Teresa and P. Pérez street shave allowed us to discover two signifícate buldings associated to the graves. One of them probably was a Celia memoria memoria on ahind of religions chapel with funerary ends. The other bulding is a panteón of Formae loculi. Both buldings allow to establish a firts at tempt to explain the relligious and social expectatives of this population relationship with the garum production.